“GAYA BELAJAR PESERTA DIDIK BERPRESTASI DALAM PEMBELAJARAN EKONOMI DI SMA KRISTEN MAKEDONIA NGABANG” - Jesica Febrianti Dewi; Gracia Sandu Inndona; Irmawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study analyzes learning styles of high-achieving students in economics learning at SMA Kristen Makedonia Ngabang. The research background concerns the importance of understanding learning styles to optimize the learning process, especially for students who demonstrate high academic achievement. The purpose of this research was to describe in-depth the dominant learning styles of high-achieving students and to identify factors that shape the learning styles of high-achieving students and their implementation. This study employed a qualitative approach with case study methods. The research subjects were 10 high-achieving students from grade XI at SMA Kristen Makedonia Ngabang, with 1 additional informant, namely the economics teacher. Data collection was conducted through semi-structured interviews, participatory observation, and documentation studies. The collected data was analyzed using data reduction, data presentation, and conclusion drawing. The findings revealed that high-achieving students at SMA Kristen Makedonia Ngabang have diverse learning styles, with kinesthetic learning style domination and combinations of visual-kinesthetic and auditory-kinesthetic. The factors shaping their learning styles are divided into internal and external factors. Internal factors include: motivation and interest, learning habits, and experience participating in economics competitions. External factors include: dormitory environment, school and teacher roles. The implementation of learning styles found that kinesthetic students are most effective learning through practice and direct activities such as role-playing, visual-kinesthetic students tend to understand material through observation of graphs and direct simulation, while auditory-kinesthetic students learn by listening to teacher explanations then conducting market simulations